Typology of Woodcarving Motifs in Johor Traditional Malay Houses - Yusof, Hanita; Sabil, Azmal; Hanapi, Amalina (International Journal of Sustainable Construction Engineering and Technology, 2023)
Johor traditional Malay houses are typically known for its Limas roof. However, apart from the significant roof, woodcarving motifs found in Johor traditional Malay houses also possess a distinct architectural heritage that can promote the identity of a region. Many woodcarving motifs are found and should be studied and managed to sustain the identity of a local region as part of heritage sustainable management. A study on typology of woodcarvings motifs is critically needed in order to avoid losing the authenticity of each state if not being preserved and documented. Johor traditional Malay houses are being demolished day by day before we get to know the typology of it’s woodcarving motifs. The objective of this paper is to identify the woodcarvings motifs found in Johor traditional Malay houses, reveal the typology and analyze the mostly used to be named as the identity of Johor woodcarving motif. Site visits were conducted to 60 traditional Malay houses around Johor in which the woodcarvings motifs were examined, photographed and documented. Interviews were also conducted with the house owners or occupants, and the wood carvers. The samples were analyzed, and the results were verified by experts. A total of 12 typologies derived from 13 motifs were discovered, drawn, coded and named. The pumpkin motif preceded the percentage of the analysis statistics of mostly used and was named as Labu Maya. The findings of this research suggest that the Labu Maya motif represents the identity of woodcarving motifs of Johor traditional Malay houses. From the analysis and discussion made, 12 typologies on Johor woodcarving motifs were revealed, named and documented. This research has shown the local authenticity, beautiful heritage that should be enhanced through managing the typology and sustaining the local identity as part of sustainable management. All these typologies are important for Johor architectural heritage, body of knowledge and also for tourism purposes.